MENANAMKAN NILAI-NILAI RELIGIUS MELALUI PELAKSANAAN KEGIATAN KEAGAMAAN JUM`AT IBADAH DI SDN SARUNI 1 - Syauqiyyah, Yasyifa Azhar; Hakim, Zerri Rahman; Hatima, Yoma (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to describe the planning, implementation, and supporting as well as inhibiting factors of the Friday Worship Program in instilling religious values at SDN Saruni 1. The research employed a qualitative descriptive approach, with data collected through interviews, observations, and documentation. The data analysis technique used Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The results of the study show that the planning of the Friday Worship Program at SDN Saruni 1 begins with preparing activities that support the cultivation of religious values, organizing schedules, and providing the necessary facilities and infrastructure. The implementation of the program varies each week, including activities such as reciting Yasin and tahlil, performing Dhuha prayers, and reading the Qur’an. These are followed by student-led sessions from Grades V or VI, which include serving as masters of ceremony, Qur’an recitation, delivering speeches, and chanting shalawat. The activities conclude with charity contributions and prayer. Supporting factors include the leadership of the principal, adequate facilities, student involvement, commitment from Islamic education teachers, and parental support. In contrast, the inhibiting factors involve student discipline issues and limited facilities for large-scale implementation.